BUDAYA KESELAMATAN DALAM UPAYA MENCAPAI “ ZERO ACCIDENT “ - Oce Prasetya (Institut Transportasi dan Logistik Trisakti, 2015)
In recent years, the world has witnessed a growing concern over the issue of safety culture within aviation and other complex, high-risk industries. The purpose of this study is to find out the roles of safety culture from safety behavior with the system of safety to reach zero accident. The method used in this study is case research or field study, with descriptive explanation, quantitative and qualitative data. Quantitative data had been gathered from the calculation of safety percentage level (Cooper) while qualitative data was taken from observation and field interviews.The highest percentage for safety at GSE is 95% and the lowest is 52.5%. The whole result shows that safety above 50% means that there’s still awareness of safety behavior by using Personal Protective Equipment (PPE) and this still needs to be maximized more. Organization safety system is already executed and well documented even though deviations are still found in the operation execution.It is hoped that this study will enable researchers and safety professionals to have a better understanding and assess safety culture which will facilitate the sharing of information and strategies for improving safety culture across organizations and industries.